Resolution of painful trichodysplasia spinulosa with topical cidofovir: case report - Kevin M. Burningham; Ritu N. Swali; Peter L. Rady; Anisha B. Patel; Stephen K. Tyring (Taylor & Francis Group, 2024)
AbstractPurpose: Trichodysplasia spinulosa (TS) is a rare, disfiguring skin condition which presents with widespread asymptomatic or pruritic, skin-colored papules with white protruding keratin spiculations in immunocompromised individuals. Due to its rarity, there is little data to guide treatment decisions. The purpose of this article is to report a case of TS that completely resolved after treatment with topical cidofovir.Materials and methods: A 19-year-old immunosuppressed female presented with widespread painful, itchy bumps on the nose and face. Upon examination, there were erythematous papules with hyperkeratinized spicules affecting the central face. Biopsy of the lesions was consistent with TS which was confirmed via PCR analysis. The tenderness of this patient's eruption was highly atypical for TS. Once daily topical application of compounded 1% cidofovir cream was prescribed.Results: The patient's symptoms resolved completely after 4 weeks of therapy with topical cidofovir 1% cream, without reduction of immunosuppression.Conclusions: Topical cidofovir 1% cream may be a valuable treatment for this rare disease.